The relationship of intrinsic, extrinsic, and quest religious orientations to Jungian psychological type among churchgoers in England and Wales - Ross, Christopher F.J. (Mental health, religion & culture, 2010)
Employing the New Indices of Religious Orientation (NIRO), this study examines the theory that different religious orientations are related to individual differences in psychological type as developed by Carl Jung and operationalized by the Myers-Briggs Type Indicator (MBTI). Data provided by 481 weekly churchgoing Christians who completed the MBTI and the NIRO demonstrated that quest religious orientation scores were higher among intuitives than among sensers, but were unrelated to introversion and extraversion, thinking and feeling, or judging and perceiving; that intrinsic religious orientation scores were higher among extraverts than introverts, higher among sensers than intuitives and higher among feelers than thinkers, but unrelated to judging and perceiving; and that extrinsic religious orientation scores were unrelated to any of the four components of psychological type. The findings relating to Jungian psychological type differences are applied in order to elucidate the psychological significance of extrinsic, intrinsic, and quest orientations to religion.